Research of Deicing and Melting Snow on Airport Asphalt Pavement by Carbon Fiber Heating Wire - Xin Su; Yong Lai; Yan Liu; Daoxun Ma; Peng Wang (Advances in Materials Science and Engineering)
In the paper, the method of deicing and melting snow by the carbon fiber heating wire (CFHW) embedded in the airport asphalt pavement is proposed to improve the security of airport operation. The field experiment of deicing and melting snow on the airport asphalt pavement is conducted. Deicing and melting snow, asphalt pavement temperature, ice-free area ratio, and snow-free area ratio are analyzed. Electrical power with 350 W/m2 is input to the airport asphalt pavement for deicing and melting snow by the CFHW. In the experiment, 3 mm ice can be melted, and the average infrared ray temperature (IRT) of the airport asphalt pavement surface can achieve an increment of 13.0°C in 2.5 hours when the air temperature is from −7.5°C to −2.2°C. Snow with 3.2 mm precipitation can be melted in 2 hours when the air temperature is from −4.8°C to −3.5°C, and the asphalt pavement temperature can achieve an increment of 5.9°C at the depth of 0.5 cm. The results show that the method of deicing and melting snow on the airport asphalt pavement by the CFHW is practicable in the cold zone.